Prosedur Pelaksanaan Perkawinanmenurut Hukum Adat Napu - Fitri Aiman Tole; Manga Patila; Rosnani Lakunna (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to determine and analyze the procedures for conducting traditional marriages according to Napu customary law. The research method used is empirical juridical research. The results indicate that Napu customary law plays a significant role in regulating marriages through customary norms that contain moral, social, and religious values. The Napu customary marriage procedure consists of three main stages: the proposal (mekalembaki), the opening of the pinang (mobungkahi embe pepamboli), and the customary ceremony (mampopolumao ada posamboko), which involves the family and traditional leaders as a form of customary legalization. If a marriage does not comply with customary marriage procedures according to Napu customary law, the resolution is carried out through customary institutions led by the customary leader, with sanctions imposed in the form of payment of customary money, provision of livestock, and communal meals. These sanctions aim to restore social balance and maintain harmony in community life. Thus, Napu customary marriage is part of the customary legal system that is still alive and relevant within the national legal framework. Keywords: Napu Custom, Customary Law, Marriage.